DIFFERENTIALS IN PROFITABILITY AND EFFICIENCY OF COWPEA MARKETING IN RURAL, SEMI- URBAN AND URBAN MARKETS IN NASARAWA STATE, NIGERIA (American International Journal of Agricultural Studies, 2023)
This study analyzed differentials in profitability and efficiency of cowpea marketing in rural semi-urban and urban markets in Nasarawa State, Nigeria. Multistage sampling technique was employed for this study. Data was collected from 150 sampled cowpea marketers through the use of well-structured questionnaires. The following statistical and econometric tools was used to achieve the stated objectives of the study, Descriptive statistics, Budgetary technique, Multinomial logit regression model and Likert scale. The results of the socioeconomic characteristics of the samples cowpea marketers show that the mean age of the sampled cowpea marketers operating in rural, semi-urban and urban markets were 35 years, 33 years and 35 years respectively. The gross margin obtained by rural marketers was N680,744.91, while the gross margin obtained by the semi-urban and urban marketers was N209,539.45 and N2,498,189.69 respectively. The marketing efficiency level achieved by the marketers were 38%, 16% and 35% and were all less than 1. The mean price of the cowpea in Naira/50kg at the various market under study were rural market price N20,909.64, semi-urban market price was N21,439.65 and urban market price was found to be N22,954.96 on average basis. The results further show that the following factors influencing the choice of rural semi-urban and urban market were age of the marketers (P